Improvement of Diabetes Mellitus After Colorectal Cancer Surgery: A Retrospective Study of Predictive Factors For Type 2 Diabetes Mellitus Remission and Overall Survival - Peng, Dong; Liu, Xiao-Yu; Cheng, Yu-Xi; Tao, Wei; Cheng, Yong (Frontiers in Oncology, 2021)
Purpose The purpose of the current study was to evaluate the impact of colorectal cancer (CRC) surgery on type 2 diabetes mellitus (T2DM) and to analyze the change in T2DM on overall survival after CRC surgery. Methods Patients who underwent CRC surgery were retrospectively enrolled from January 2013 to December 2019. The status of T2DM pre- and 1-year after CRC surgery was recorded, and predictive factors for T2DM remission and overall survival were analyzed. Results A total of 296 patients were included in this study. Thirty-eight patients experienced remission of T2DM 1 year after CRC surgery, and the remission rate was 12.8%. Weight loss was significantly higher in the T2DM remission group (p=0.038), and the T2DM duration was significantly shorter in the T2DM remission group (p=0.015). In the multivariate logistic regression analysis, higher weight loss (p=0.046, odds ratio=1.060, 95% CI=1.001-1.122) and shorter T2DM duration (p=0.019, odds ratio=1007, 95% CI=1.001-1.014) were predictive factors for remission of T2DM. Furthermore, in multivariate Cox regression analysis, lower TNM stage (p=0.000, odds ratio=2.147, 95% CI=1.474-3.128) and T2DM remission (p=0.033, odds ratio=2.999, 95% CI=1.091-8.243) were the predictive factors for better overall survival. Conclusion Patients with concurrent CRC and T2DM had a 12.8% remission 1 year after CRC surgery. Higher weight loss and shorter T2DM duration contributed to T2DM remission, and patients with T2DM remission could improve in terms of their overall survival.